Efektivitas Penggunaan Metode Karyawisata dalam Proses Pembelajaran Kurikulum 2013 - Primanita Sholihah Rosmana; Sofyan Iskandar; Mila Oksanti; Siti Aulia Khasanah; Widia Triyana (AS-SABIQUN, 2022)
In the educational process, the existence of learning activities is a major part of the learning process. In the learning process, optimal learning outcomes can be achieved by students are able to interpret learning well and students can experience it directly. So that teachers need to prepare strategies and learning methods that can improve student learning outcomes, one of which is the field trip learning method. The purpose of this study is to find out and understand the effectiveness of using the field trip learning method for elementary school students. The type of research used in this research is descriptive qualitative using the questionnaire method. From the diagram of the effectiveness of the field trip method, 45.7% of respondents agree or think that the use off the field trip method is effective in supporting the learning process. And most respondents as much as 54.3% considered that the use of the field trip method might have a good influence on the learning process.